(3ebOeI aj PcQ efGbH CejQ GdeDefjf Ydi Hf CHj WGdHs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s
(3ChdgG (B:s
(3Yf eMeO Hf jYbhH UdhGJ Gddg Ydjge bGd eDda GdcJGH Gf NjQ GdNdb hGdChdjf ge fhM hGHQGgje hSdjeGf hGjhH s
(3BNQgG (B:s
(3hbGd ai Mb Ydi Ydjg GdSdGe hjWYehf GdWYGe Ydi MHg eScjfkG hjJjekG hGSjQG gPG eKdg eY GdChdjf Ydjge LejYkG GdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3GfXQg eY GdeNWhW Qbe (B252 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf s
Keywords: (3GdJGQjNs